2014
DOI: 10.3892/ijmm.2014.1852
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin protects against high glucose-induced damage in bone marrow-derived endothelial progenitor cells

Abstract: Endothelial progenitor cells (EPCs), a group of bone marrow-derived pro-angiogenic cells, contribute to vascular repair after damage. EPC dysfunction exists in diabetes and results in poor wound healing in diabetic patients with trauma or surgery. The aim of the present study was to determine the effect of quercetin, a natural flavonoid on high glucose‑induced damage in EPCs. Treatment with high glucose (40 mM) decreased cell viability and migration, and increased oxidant stress, as was evidenced by the elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 42 publications
4
18
0
2
Order By: Relevance
“…As expected, NAM efficiently inhibited the beneficial effect of quercetin on ROS scavenging, suggesting that the effect of quercetin on ROS clearance is SIRT-dependent. Recently, SIRT1, 2, and 3 were shown to be important for spindle organization and mitochondrial distribution in mouse oocytes [11, 12, 25, 27]. We also found that quercetin treatment reduced the frequency of spindle defects and altered the mitochondrial distribution, further supporting our conclusion that quercetin protects oocytes from postovulatory oocyte aging in a SIRT-dependent manner.…”
Section: Discussionsupporting
confidence: 88%
“…As expected, NAM efficiently inhibited the beneficial effect of quercetin on ROS scavenging, suggesting that the effect of quercetin on ROS clearance is SIRT-dependent. Recently, SIRT1, 2, and 3 were shown to be important for spindle organization and mitochondrial distribution in mouse oocytes [11, 12, 25, 27]. We also found that quercetin treatment reduced the frequency of spindle defects and altered the mitochondrial distribution, further supporting our conclusion that quercetin protects oocytes from postovulatory oocyte aging in a SIRT-dependent manner.…”
Section: Discussionsupporting
confidence: 88%
“…In vitro short-term exposure of EPCs to high-glucose, which impairs their number and functionality, determines SIRT1 downregulation, reduces FOXO1 deacetylation, and reduces eNOS phosphorylation (Fig. 4) (15,220). Consistent with these findings, in vitro and ex vivo studies demonstrate that poor glycemic control in type 2 diabetes patients reduces number of EPCs and differentiation capability by blocking SIRT1 signaling (3,17,116).…”
Section: Fig 4 Sirt1 and Sirt6 During Altered Glucose Homeostasis supporting
confidence: 53%
“…; Zhao et al . ). We found that SIRT1 protein abundance was increased 2.5‐ and 2.0‐fold in mdx and mdxQ, respectively, compared to C57.…”
Section: Resultsmentioning
confidence: 97%